Clinical and MRI study of brain stem and cerebellar involvement in Japanese patients with multiple sclerosis - Nakashima, I. (BMJ Group, 1999)
OBJECTIVES—To investigate the clinical and MRI features of brain stem and cerebellar lesions in Japanese patients with multiple sclerosis. METHODS—A retrospective study of 66 consecutive Japanese patients with multiple sclerosis (42 women and 24 men) was done by reviewing the medical records and MRI films. Forty nine patients were diagnosed as having clinically definite multiple sclerosis and 17 patients as having clinically probable multiple sclerosis according to Poser's criteria. Prevalence rates of each brain stem and cerebellar manifestation and frequency and distribution of MRI lesions in these patients were studied. RESULTS—Forty three patients (65%) had one or more infratentorial manifestations. Cranial nerves were clinically involved in 28 patients (42%), and most of the lesions were identified by MRI. Among them, manifestations of facial, trigeminal, and abducens nerves were relatively common. Cerebellar ataxia was found in 20 patients (30%). The MRI study showed that the lesions responsible for ataxia in these patients were mainly found in the cerebellar peduncles, but cerebellar hemispheric lesions were detected in only four patients (6.4%). CONCLUSION—The low frequency (6.4%) of the cerebellar MRI lesions in these patients is in sharp contrast with the figures reported for white patients with multiple sclerosis (50%-90%). Racial and genetic differences may have an influence on the susceptibility of each part of the CNS to demyelination in multiple sclerosis.